Lymphangiectatic oro-facial and ano-genital granulomatosis. Its relationship with Crohn’s disease - Salerno, V.; Mangione, A.; Garofalo, L.; Bonifazi, E. (European Journal of Pediatric Dermatology, 2012)
Oro-facial and ano-genital granulomatosis represent two aspects of the same chronic inflammatory disorder probably related with Crohn’s disease. In this paper we describe three pediatric cases of granulomatosis, one oro-facial and two ano-genital; the second of these two cases was followed after years of observation by full-blown Crohn’s disease. On the basis of personal data and review of the literature we emphasize the importance of lymphangiectasias, often visible not only histologically but also clinically, for proper diagnosis of the disease.